FLUORITE AS AN INDICATOR OF INTERNAL ZONING AND ORE POTENTIAL OF RARE METAL GRANITES OF THE ORLOVSKOE TANTALUM DEPOSIT, EASTERN TRANSBAIKALIA - Kukushkina O.A.; Matias V.V. (My University, 2004)
This study is devoted to accessory fluorite in granites of the Western Massif of the Khangilai pluton, eastern Transbaikalia. This mineral is widespread in Ta-Nb-bearing granites of the Orlovskoe ore deposit. Tantalum-bearing and barren phases of the granites, as well as their varieties with different concentrations of major and ore elements, were sampled at the ore deposit. Fluorite from these samples was studied by photoluminescene, thermoluminescence, EPR, neutron activation, and spectral analysis. Specific features were determined for fluorite from Ta-bearing and barren granites of various intrusive phases and zones of the deposit differing in major-element chemistry and ore potential. The reliability of the conclusions was verified by criteria of nonparametric statistics.